2018
DOI: 10.4108/eai.13-7-2018.161408
|View full text |Cite
|
Sign up to set email alerts
|

Workflow scheduling and reliability improvement by hybrid intelligence optimization approach with task ranking

Abstract: Workflow scheduling is one of the most challenging tasks in cloud computing. It uses different workflows and quality of service requirements based on the deadline and cost of the tasks. The main goal of workflow scheduling algorithm is to optimize the time and cost by using virtual machine migration. This algorithm computes the subset problem and decision problem in NP time. It works on the decision-making process to reduce the time and cost of computation on the server side. This paper proposes hybrid optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It used PEFT based heuristic algorithm for initialization of the population. 41 The proposed approach reduces the random initialization of the tasks in the workflow.…”
Section: Proposed Nature-inspired Heuristicmentioning
confidence: 99%
See 1 more Smart Citation
“…It used PEFT based heuristic algorithm for initialization of the population. 41 The proposed approach reduces the random initialization of the tasks in the workflow.…”
Section: Proposed Nature-inspired Heuristicmentioning
confidence: 99%
“…It proposed hybrid enhancement to enhance the efficiency and utilization of virtual machines by considering local and global optimization policies. It used PEFT based heuristic algorithm for initialization of the population 41 . The proposed approach reduces the random initialization of the tasks in the workflow.…”
Section: Proposed Nature‐inspired Heuristicmentioning
confidence: 99%
“…The hybridization of the GWO and GA algorithm was proposed by Bouzary and Frank 33 who found that the proposed algorithm is superior to GWO and GA in terms of cost. Khurana and Singh 34 have introduced a hybrid of flower pollination algorithm and GWO to reduce the cost and time and provide efficient results in comparison to flower pollination with GA. Table 1 summarizes some existing scheduling algorithms proposed in cloud computing.…”
Section: Related Workmentioning
confidence: 99%
“…The simulation results proved that the ACO outperforms traditional FCFS and Round-Robin algorithms. The authors [14] developed a hybrid optimization technique using Flower Pollination and Grey Wolf Optimization. The PEFT algorithm was used for the initialization of the proposed method for workflows.…”
Section: Related Workmentioning
confidence: 99%